2013
DOI: 10.1115/1.4007583
|View full text |Cite
|
Sign up to set email alerts
|

Large-Eddy Simulation of Film Cooling in an Adverse Pressure Gradient Flow

Abstract: In order to analyze the interaction of multiple rows of film cooling holes in flows at adverse pressure gradients, large-eddy simulations (LESs) are performed. The considered three-row cooling configuration consists of inclined cooling holes at an angle of 30 deg with a lateral pitch of p/D=3 and a streamwise spacing of l/D=6. The cooling holes possess a fan-shaped exit geometry with lateral and streamwise expansions. For each cooling row the complete internal flow is computed. Air and CO2 are injected in orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 30 publications
2
6
0
Order By: Relevance
“…Detached-eddy simulation (DES), which operates as URANS in boundary layers and LES away from walls, is used by Kim and Hassan (2010) and Foroutan and Yavuzkurt (2015). Implicit sub-grid scale modelling, where numerical dissipation is assumed to account for unresolved turbulent dissipation, is also used by some authors (Guo et al, 2006;Konopka et al, 2013;Muldoon and Acharya, 2006;Oliver et al, 2017;Renze et al, 2008).…”
Section: Computational Modelling Of Film Coolingmentioning
confidence: 99%
See 1 more Smart Citation
“…Detached-eddy simulation (DES), which operates as URANS in boundary layers and LES away from walls, is used by Kim and Hassan (2010) and Foroutan and Yavuzkurt (2015). Implicit sub-grid scale modelling, where numerical dissipation is assumed to account for unresolved turbulent dissipation, is also used by some authors (Guo et al, 2006;Konopka et al, 2013;Muldoon and Acharya, 2006;Oliver et al, 2017;Renze et al, 2008).…”
Section: Computational Modelling Of Film Coolingmentioning
confidence: 99%
“…required number of grid points for a successful simulation. However, recent studies with second-order codes have used approximately 15 million points (Konopka et al, 2013;Zhong et al, 2016).…”
Section: Computational Modelling Of Film Coolingmentioning
confidence: 99%
“…Their main focus was on the interaction of an acoustic wave with the coolant jets rather than the cooling effectiveness. Konopka et al [13] analysed the interaction of multiple rows of coolant jets using LES.…”
Section: Introductionmentioning
confidence: 99%
“…Zhong et al (2016) indicated that a steady core with low-temperature variance appears near the exit of the round hole, and high-temperature variance appears around this steady core. However, in large eddy simulation (LES) results from Renze et al (2008), Guo et al (2006) and Konopka et al (2013), hairpin vortexes are replaced by a large number of broken vortexes, and horseshoe vortexes also become unobvious. It might be because that, in these cases, the mainstream turbulent boundary layer is fully-developed before reaching the discharged hole.…”
Section: Introductionmentioning
confidence: 99%